Strengthening agricultural extension training: Process skills and competency gaps in undergraduate agricultural extension curriculum in South Africa - von Maltitz, Lindie; Davis, Kristin E.; Suvedi, Murari; Chanza, Charity; Agwu, Ekwe Agwu; Sasidhar, P. V. K.; Ukamaka, Mabel Dimelu; Liverpool-Tasie, Lenis Saweda; Anugwa, Ifeoma Quinette; Tchuwa, Frank (Michigan State University Press, 2023)
Assessment of process skills and competency gaps in undergraduate (UG) agricultural extension curriculum can assist in developing competency-based curricula which in turn could enhance the efficiency of agricultural extension and advisory services (AEAS) in South Africa. The Michigan State University Alliance for African Partnership (AAP) launched a multi-country study to contribute to upgrading and tailoring the agricultural extension curricula at participating institutions. The research aims to identify skills and competency gaps in undergraduate agricultural extension curricula in the participating countries – Kenya, Malawi, Nigeria, South Africa and Uganda - and use the results to contribute to formulating appropriate curricula. The research questions are: 1. Do extension programs effectively address the needs of current food and agricultural systems? 2. What are the critical job skills and core competencies required of extension workers to effectively plan, implement, and evaluate extension work in today’s changing context? 3. Does the undergraduate curriculum in extension education include education and/or training on these job skills or core competencies? 4. What are the barriers to effectively training extension workers with required core competencies, and how can these barriers be removed? The study undertaken in the above participating countries assessed 11 process skills and competencies: program planning, program implementation, communication and public relations, information and communication technologies (ICTs), program evaluation, personal and professional development, diversity and gender, technical subject matter expertise, marketing, brokering and value chain development, soft skills and nutrition skills and competencies. These were assessed qualitatively using focus group discussions (FGDs) and quantitatively using an online questionnaire with two Likert scale based questions: “How important is this skill or competency for an extension worker?” and “How well does the undergraduate extension curriculum cover this competency?”.